Fiber Optics in Medicine Module - Mary Lowe; Nancy Donaldson; Alex Spiro; Charles Gosselin; Mark Nadeau (Association of American Medical Colleges, 2015)
Abstract Fiber optics is an important light collection and delivery system in medical endoscopic and laser surgery procedures. In order to scaffold student understanding in fiber optics, and addresses specific competencies in Scientific Foundations for Future Physicians: Report of the Association of American Medical Colleges and the Howard Hughs Medical Institute Committee, this activity incorporates active learning and inquiry-based pedagogies. Learners should have a prerequisite knowledge of geometric optics at the level of an introductory undergraduate physics course and desire to broaden their understanding of applications of physics to medicine. Therefor the target audience includes those pursuing graduate school in medicine, health care, or medical physics. The material is divided into six sections addressing the following areas: basic principles (i.e., acceptance angle, numerical aperture, wave guiding), illumination, coupling, loss/attenuation, and viewing. Learning objectives, assessment questions, additional problems, and solutions are included in each section. Module activities were designed to elicit student interest with medical case studies, hands-on activities, and laboratory optics work interspersed with guided inquiry-based questions, in addition to outside reading and writing, and lecture. This module has been deployed in an intermediate-level undergraduate physics class. Students tended to be highly engaged while doing the activities. Based on assessment data, we have found that a hands-on, active-learning results in good knowledge retention by students. Ending each class with a content tie-up was helpful in reducing the amount of didactic lecturing and allowing students to make connections from hands-on work.